2022
DOI: 10.1155/2022/6400227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ferroptosis-Related Gene Prognostic Signature and HSF1 for Reversing Doxorubicin and Gemcitabine Resistance in Uterine Carcinosarcoma

Abstract: Purpose. Iron metabolism and ferroptosis play crucial roles in the pathogenesis of cancer. In this study, we aim to study the role of ferroptosis-related genes (FRGs) in uterine carcinosarcoma (UCS) and identify potential target for UCS. Methods. Prognostic differentially expressed FRGs were identified of in the TCGA cohort. Integrated analysis, cox regression, and the least absolute shrinkage and selection operator (LASSO) methods of FRGs were performed to construct a multigene signature prognostic model. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Ferroptosis is an iron-dependent, programmed cell death process. Extensive research has demonstrated a close association between ferroptosis and GEM resistance in various tumor types, including PDAC [4,8,37]. Although there is currently no research linking BUB1 to ferroptosis, our study found that treatment of PC cells with the ferroptosis inducer Erastin significantly downregulates the expression of BUB1.…”
Section: Discussionmentioning
confidence: 47%
“…Ferroptosis is an iron-dependent, programmed cell death process. Extensive research has demonstrated a close association between ferroptosis and GEM resistance in various tumor types, including PDAC [4,8,37]. Although there is currently no research linking BUB1 to ferroptosis, our study found that treatment of PC cells with the ferroptosis inducer Erastin significantly downregulates the expression of BUB1.…”
Section: Discussionmentioning
confidence: 47%
“…SHARPIN, an activator of NF-kappaB, can also induce the ferroptosis of synovial sarcoma cells, and the PGC1α/NRF2/SLC7A11 axis and BNIP3L/NIX-mediated mitophagy is involved in its downstream regulation [ 203 ]. Moreover, in the case of uterine carcinosarcoma, knocking out the ferroptosis-related gene named heat shock factor 1 (HSF1) increased the sensitivity of tumor cells to treatment with adriamycin or gemcitabine, suggesting a potential combination therapy approach [ 204 ]. These findings underscore the versatility of ferroptosis-based treatments across different types of sarcomas.…”
Section: Progress Of Research On Ferroptosis In Sarcoma Treatmentmentioning
confidence: 99%
“…In uterine cancer sarcoma cells, HSF1 knockdown increases lipid ROS and iron levels, inhibits cell growth, and promotes sensitivity to doxorubicin and gemcitabine treatment. Targeting HSF1 thus reverses drug resistance of doxorubicin and gemcitabine in uterine cancer sarcoma via the ferroptosis pathway ( 26 ).…”
Section: Fbxw7 Ubiquitinates Its Downstream Substrates To Regulate Dr...mentioning
confidence: 99%